Pandawa Beach Marketing Strategy 4.0 during the Covid-19 Pandemic - Ida Ayu Putu Sulistya; I Putu Astawa; Ni Gusti Nyoman Suci Murni; I Ketut Sutama; I Made Darma Oka (International Journal of Glocal Tourism, 2021)
Abstract: Purpose: The purpose of this study is to introduce more aggressively the existing situation of Pandawa Beach (Pantai Pandawa) in Badung, Bali, Indonesia, by implementing a marketing strategy 4.0 during the Covid-19 pandemic. Research methods: The primary data of this study are from observations and interviews with the community and tourism destination managers and other informants who were determined by the snow ball method. The secondary data for this study are from literature study and documentation. Findings: To increase the number of visits during the pandemic, it is necessary to provide more intensive information about the existence, programs, and attractions provided by Pandawa Beach management. The implementation of marketing strategy 4.0 for Pandawa Beach is very important. It is carried out with the 5A component strategy, namely Aware, Appeal, Ask, Act, and Advocate. Implication: Pandawa Beach Managers are expected to be able to promote and provide appropriate information to the public through offline and online (social media networks) so that later it will become an attraction for tourist arrivals during the pandemic.